Variasi Morfologi Bambu Tali [Gigantochloa apus (Schult.F.) Kurz.] pada berbagai ketinggian tempat di Sub Daerah Aliran Sungai Pelus - Tria Fauzi Prabandani Hakim; Pudji Widodo; Eming Sudiana (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2015)
A study on the morphological variation of tali bamboo [Gigantochloa apus (Schult.f.) Kurz] has been conducted at various altitudes of Sub Watershed Pelus Banyumas, Central Java. This study was aimed at determining the morphological variations in relation to altitudes above sea levels. The method used was survey with stratified sampling.  The variables measured included culm diameter, culm internode length, culm sheath length and width, ovate-triangular blade length and width, leaf blade length and width, stem color and hairs, and altitude. The results of this study indicated that the altitudinal difference effect some morphological characteristics of tali bamboos such as: 1) green young seedling with black hairs found at 200-299 m and 300-399 m asl. 2) morphological variations are effected by altitude. Tali bamboo grows optimally at the altitude of 400 to 499 m asl. The results of regression analysis showed that the altitude has a relatively close correlation with somes of morphological character of tali bamboo.